2014
DOI: 10.1038/ncomms6043
|View full text |Cite
|
Sign up to set email alerts
|

Termination chemistry-driven dislocation structure at SrTiO3/MgO heterointerfaces

Abstract: Exploiting the promise of nanocomposite oxides necessitates a detailed understanding of the dislocation structure at the interfaces, which governs diverse and technologically relevant properties. Here we report atomistic simulations demonstrating a strong dependence of the dislocation structure on the termination chemistry at the SrTiO 3 /MgO heterointerface. The SrO-and TiO 2 -terminated interfaces exhibit distinct nearest neighbour arrangements between cations and anions, leading to variations in local elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 51 publications
5
59
0
Order By: Relevance
“…This is somehow expected considering the moderate temperature at which the annealing is carried out. This phenomenon is indicative of a strongly preferential incorporation of hydroxyl groups in the core of the MDs, as predicted by recent theoretical studies . This incorporation is accompanied by absorption of protons necessary to maintain the neutrality of the electrical charge.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is somehow expected considering the moderate temperature at which the annealing is carried out. This phenomenon is indicative of a strongly preferential incorporation of hydroxyl groups in the core of the MDs, as predicted by recent theoretical studies . This incorporation is accompanied by absorption of protons necessary to maintain the neutrality of the electrical charge.…”
Section: Discussionsupporting
confidence: 75%
“…It was hypothesized the high values of conductivity were possibly related to the high densities of defects, mostly dislocations, at the film/substrate interface. Namely, dislocation lines can act as fast paths for diffusing atoms, similar to the pipe diffusion mechanism, which has been predicted in the case of the SrTiO 3 /MgO interface . This phenomenon is thought to originate from the disordered core region with high mobility for cation diffusion .…”
Section: Introductionmentioning
confidence: 56%
“…Furthermore, high-resolution transmission electron microscopy examination in other materials, in particular the interface of (Nd 0.35 Sr 0.65 )MnO 3 /SrTiO 3 , demonstrated that edge-type misfit dislocations allow for interdiffusion of cations within a semicylindrical boundary around the dislocation 7 , as also predicted for the dislocations of ceria in this work. The edge dislocation modelled in this paper can be different from misfit dislocations at the thin-film/substrate interfaces due to the local structure and chemical composition 49 . However, the key driver of cation and vacancy segregation around the edge dislocations in bulk ceria studied here is the strain field, which is also present around misfit dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the structure of oxide/oxide or metal/oxide interfaces is much more difficult to assess. Such interfaces are often several nanometers wide [69], exhibit transitions in structure reminiscent of phase changes [8], and contain intrinsic defects with distinct local compositions [70]. NR provides several advantages for investigating such interfaces, including high depth resolution and sensitivity to composition.…”
Section: Fe/y 2 O 3 Interface: Sensitivity To Magnetization and Complmentioning
confidence: 99%